The Need for Aristotle in Contemporary Science - Müürsepp, Peeter (Problemos, 2003)
In 17th century Aristotle was proclaimed outdated and uninteresting from the point of view of advancement of knowledge. This attack was mostly aimed at logic. The attackers did not notice the principal difference of the physical and metaphysical works of the Stagirite from his logic. Only in the last decades of XX-th century the idea of the two different Aristotles began to gain recognition. First of all we should thank Daniel W. Graham for this development. It is René Thom, however, who has presented a consistent conception about the need for the application of Aristotelian approach in contemporary science. Despite bringing up the excellent idea of connecting materialism with finality, R. Thom has failed to understand the real meaning of the Stagirite’s system of four causes.
Keywords: Aristotle; René Thom; finality; causality; intelligibility